Social Status and Public Expectations: Self-Selection of High-Skilled Migrants - Claudia Lumpe; Christian Lumpe (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We analyze public expectations about migrants' provision of work effort as a driving force in the self-selection process of high-skilled migrants. We adopt and extend Piketty's (1998) theoretical framework of social status and work out how country-specific public expectations affect the migrants' choice about their country of destination. As a result, we relate Germany's attested low attractiveness for high-skilled immigrants to its society's attitudes towards immigrants. We develop measures to increase Germany's attractiveness in the competition about talents.
Keywords: F22; F16; F66; 330